How might patient involvement in healthcare quality improvement efforts work-A realist literature review - Carolina Bergerum; Johan Thor; Karin Josefsson; Maria Wolmesjö (Wiley, 2019)
Abstract Introduction This realist literature review, regarding active patient involvement in healthcare quality improvement (QI), seeks to identify possible mechanisms that contribute to success or failure. Furthermore, the paper outlines key considerations for organizing and supporting patient involvement in healthcare QI efforts. Methods Two literature searches were performed. Altogether, 1204 articles from a healthcare context were screened, focusing on improvement efforts that involve patients, healthcare professionals and/or managers and leaders. Among these, 107 articles fulfilled the chosen study selection criteria and were further analysed. Eighteen articles underwent a full realist review. In the realist synthesis, context‐mechanism‐outcome configurations were articulated as middle‐range theories and organized thematically to generate a program theory on how active patient involvement in QI efforts might work. Results The articles exhibited a diversity of patient involvement approaches at different levels of healthcare organizations. To be successful, organizations' support of QI efforts that actively involved patients tailored the QI efforts to their context to achieve the desired outcomes, and involved the relevant microsystem members. Furthermore, it promoted interaction and partnership within the microsystem, and supported the behavioural change that follows. Conclusion This realist synthesis generates a program theory for active patient involvement in QI efforts; active patient involvement can be a tool (resource), if tailored for interaction and partnership (reasoning), that leads to behaviour change (outcome) within healthcare QI efforts. The theory explains essential resource and reasoning mechanisms, and outcomes that together form guidance for healthcare organizations when managing active patient involvement in QI efforts.